Camera Obscura, Camera Lucida Essays in Honor of Annette Michelson - Turvey, Malcolm; Allen, Richard (Film Culture in Transition, 2003)
Annette Michelson's contribution to art and film criticism over the last three decades is unparalleled. This volume honors Michelson's unique legacy with original essays by some of the many scolars that have been influenced by her work. Some continue her efforts to develop theoretical frameworks for understanding modernist art, while others practice her form of interdisciplinary crtiticism in relation to avant-garde and modernist art works and artists. Still others investigate and evaluate Michelson's work itself. All in some way pay homage to het extraordinary contribution and demonstrate its continued centrality to the field of art and film criticism.